The Constitutionalization of Sharia in Muslim Countries: Historical and Political Struggles in Indonesia, Türkiye, and Saudi Arabia - Zada, Khamami; Faizin, Afwan; Abdillah, Akhmad Mughzi; Hifni, Ahmad; Wahyudi, Johan (Mazahib, 2025)
This study examines the complex relationship between sharia and constitutionalism in three Muslim-majority countries: Indonesia, Türkiye, and Saudi Arabia. Despite their majority Muslim population, these countries have adopted divergent approaches in integrating—or delimiting—the role of sharia within their constitutional frameworks. Drawing on interviews with legal and political scholars from each country, the research employs a comparative political-constitutional approach to analyze the dynamics of sharia constitutionalism across these distinct contexts. The findings reveal varying degrees of constitutional accommodation of sharia. Indonesia exemplifies a model of religious constitutionalism, where Islamic principles are acknowledged but not formally codified within the constitutional text. Türkiye represents a paradigm of secular constitutionalism that distinctly separates religion and state, excluding sharia from the constitutional and legal order. In contrast, Saudi Arabia exhibits a puritan constitutionalism, whereby the Quran and Hadith constitute the primary sources of constitutional authority. These contrasting models illuminate broader ideological and institutional orientations: Saudi Arabia grounds its constitutional identity in religion, Indonesia integrates certain religious principles within a pluralistic framework, and Türkiye maintains a secularist stance that confines religion to the private sphere.